Uncovering protein glycosylation dynamics and heterogeneity using deep quantitative glycoprofiling (DQGlyco) - Potel, Clément M.; Burtscher, Mira Lea; Garrido-Rodriguez, Martin; Brauer-Nikonow, Amber; Becher, Isabelle; Le Sueur, Cecile; Typas, Athanasios; Zimmermann, Michael; Savitski, Mikhail M. (Nature structural & molecular biology, 2025)
Protein glycosylation regulates essential cellular processes such as signaling, adhesion and cell-cell interactions; however, dysregulated glycosylation is associated with diseases such as cancer. Here we introduce deep quantitative glycoprofiling (DQGlyco), a robust method that integrates high-throughput sample preparation, highly sensitive detection and precise multiplexed quantification to investigate protein glycosylation dynamics at an unprecedented depth. Using DQGlyco, we profiled the mouse brain glycoproteome, identifying 177,198 unique N-glycopeptides—25 times more than previous studies. We quantified glycopeptide changes in human cells treated with a fucosylation inhibitor and characterized surface-exposed glycoforms. Furthermore, we analyzed tissue-specific glycosylation patterns in mice and demonstrated that a defined gut microbiota substantially remodels the mouse brain glycoproteome, shedding light on the link between the gut microbiome and brain protein functions. Additionally, we developed a novel strategy to evaluate glycoform solubility, offering new insights into their biophysical properties. Overall, the in-depth profiling offered by DQGlyco uncovered extensive complexity in glycosylation regulation.